2019
DOI: 10.1016/j.jhsa.2018.03.045
|View full text |Cite
|
Sign up to set email alerts
|

Management of Diabetic Trigger Finger

Abstract: Diabetics have a much greater prevalence of trigger finger than nondiabetics and are more likely to have severe symptoms. Diabetic trigger finger may be more accurately described on a spectrum of diabetic hand pathology alongside carpal tunnel syndrome and cheiroarthropathy. Recent publications have called into question the current treatment algorithm for diabetic trigger finger. Although some evidence supports the use of corticosteroid injections, a recent cost analysis reported that immediate surgical releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 19 publications
1
17
0
2
Order By: Relevance
“…Ganglion cysts are the most common soft-tissue tumours of the hand and wrist occurring most commonly in young adults with a slight female predominance [ 9 , 23 ]. Similar to carpal tunnel syndrome and ganglion cysts, trigger finger is most common among women in the fifth or sixth decade of life with higher reported prevalence in those with diabetes mellitus, rheumatoid arthritis, or amyloidosis [ 10 , 12 , 24 , 25 ]. Wildin et al reported a 36% increase in primary care referral for elective hand surgery in the United Kingdom over the course of one decade with a referral rate of 112 per 100,000 patients per year for carpal tunnel syndrome and 55 per 100,000 patients per year for ganglion cysts [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ganglion cysts are the most common soft-tissue tumours of the hand and wrist occurring most commonly in young adults with a slight female predominance [ 9 , 23 ]. Similar to carpal tunnel syndrome and ganglion cysts, trigger finger is most common among women in the fifth or sixth decade of life with higher reported prevalence in those with diabetes mellitus, rheumatoid arthritis, or amyloidosis [ 10 , 12 , 24 , 25 ]. Wildin et al reported a 36% increase in primary care referral for elective hand surgery in the United Kingdom over the course of one decade with a referral rate of 112 per 100,000 patients per year for carpal tunnel syndrome and 55 per 100,000 patients per year for ganglion cysts [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Isso porque outras condições como a queiroartropatia e síndrome da mão rígida estão presentes concomitantemente com o dedo em gatilho. 16 A maioria dos casos requerem tratamento cirúrgico com a liberação a céu aberto da polia A1. 17 Esse tipo de procedimento não se enquadra para a paciente em questão, já que houve boa resposta ao tratamento conservador.…”
Section: Discussionunclassified
“…CSIs can be given subcutaneously or within the flexor tendon sheath with the use of US guidance, without measurable clinical difference 32 . Studies tend to agree that approximately 50% of all patients receiving injections will achieve resolution after a single injection, although the exact numbers vary depending on the length of follow-up and patient characteristics (e.g., there is a potential for poorer outcomes in patients with diabetes) 33 . Perhaps the best evidence for the long-term effectiveness of CSIs comes from a case series that analyzed 366 first-time injections into the flexor tendon sheath.…”
Section: Nonoperative Managementmentioning
confidence: 99%